Tinqueux 'la haubette' (Marne, France) : un site exceptionnel du Néolithique ancien - Hachem, Lamys, (Archaeopress Publishing Ltd, 2021)
This volume presents the results of archaeological work at the Neolithic site of Tinqueux 'la Haubette' (Marne) dated to the 'Blicquy/Villeneuve-Saint-Germain' (5000-4700 cal. BC). The site comprises five houses, a series of pits, and the remains of an oven. The analyses reveal hitherto unknown facets of the BVSG culture.